Conductometric Studies of Solvent Influence upon Complex Formation Between 4?-Nitrobenzo-15-crown-5 and Ni2+, Co2+ and Cu2+ in Acetonitrile-Methanol Binary Mixtures - Boosaeeidi, F.; Rounaghi, G.H.; Ghaemi, A. (Asian Journal of Chemistry, 2010)
The complex formation between Ni2+, Co2+ and Cu2+ metal cations with 4'-nitrobenzo-15-crown-5 was studied in acetonitrile (AN)-methanol (MeOH) binary systems at different temperatures using conductometric method. In all cases, 4'-nitrobenzo-15-crown-5 forms 1:1 complexes with these metal ions. The stability of the complexes is sensitive to the solvent composition and non-linear behaviour was observed for variation of log kf of the complexes versus the composition of the binary mixed solvents. The results show that the selectivity order of 4'-mitrobenzo-15-crown-5 for the metal ions in pure AN is: Co2+ > Cu2+ > Ni2+, but in the case of pure MeOH is: Ni2+ > Cu2+ > Co2+ and this selectivity order is changed with the composition of the mixed solvents. The values of thermodynamic parameters (ΔHºc, ΔSºc) for complexation reactions were obtained from temperature dependence of the stability constants and the results show that in most cases, the complexes are enthalpy stabilized, but entropy destabilized and the values of ΔHºc and ΔSºc depend strongly on the nature of the medium. A non-linear behaviour is observed between the thermodynamic parameters and the composition of the mixed solvents.